Climate‐driven change in the water sourced by trees in a de‐glaciating proglacial fore‐field, Torres del Paine, Chile. Issue 7 (26th July 2019) - Vuaridel, Marceline; Cherubini, Paolo; Mettra, François; Vennemann, Torsten; Lane, Stuart N.
Abstract: The colonization of proglacial margins by vegetation following glacier recession is a slow process, not least because glacially produced sediments are commonly well drained. Following from human‐induced climate change, warming could increase both growth rates and water availability because of glacier melting, so compensating for situations where climate change reduces precipitation. Compensation is likely a function of location, which will control access to meltwater and groundwater, themselves spatially variable. For the Olguin glacier (Torres del Paine, Chile), we test the hypothesis that as climate has warmed and precipitation has fallen, tree growth rate response is dependent upon the access of trees to glacial meltwater. Cores were taken from trees in three revegetating zones: (Z1) proglacial stream proximal, (Z3) proglacial stream distal, and (Z2) intermediate between Z1 and Z3. For trees within each zone, we measured annual tree‐ring widths and δ 2 H values. Z1 growth rates were strongly correlated with temperature and Z3 with precipitation, and Z2 showed a shift from precipitation correlation (i.e., following Z3) to temperature correlation (i.e., following Z1) through time. δ 2 H values were lowest at Z1, reflecting water of glacial origin, were highest at Z3, reflecting meteoric water supply, and shifted through time at Z2 from meteoric to glacial. Increased water supply associated with temperature‐driven glacier recession may compensate for decreasing water supply from precipitation to influence tree growth. This compensation is likely related to the spatial organization of the subsurface flux of glacial melt and leads to different revegetation processes to those envisaged in the classical chronosequence model of vegetation following glacier recession.